Genesis 2:24 : Locus classicus van monogamie in die Ou Testament? 'n Literêr-historiese ondersoek na perspektiewe op poligame huwelike in die Ou Testament - Dorey, Pieter J. (Old Testament essays, 2004)
Various Christian societies utilise Genesis 2:24 as locus classicus for monogamy. A literary-historical approach has been followed to show that Genesis 2:24 cannot serve as locus classicus for the legitimation of an exclusive monogamous marriage only. Genesis 2:24 might also be applicable to polygamous marriage forms. Practical considerations, social situations and cultural customs influenced Israel's view of marriage and determined what in their relationship with Yahweh was morally and ethically acceptable for them. This also applies to polygamous marriage. Cultural customs and moral and ethical norms and values which served to Israel as norm in their Yahweh religion, can also serve to make a custom like polygamous marriage acceptable today. Monogamy is not the only acceptable marriage form for the Christian faith.